Power plant units for CO2 neutral energy security in Switzerland - Züttel, Andreas; Nützenadel, Christoph; Schlapbach, Louis; Gilgen, Paul W. (Frontiers in Energy Research, 2024)
A new concept based on Power Plant Units, able to deliver renewable energy on demand, for the transition from fossil fuels to renewable energy in Switzerland is presented. The technically realized efficiencies showed that complete electrification leads to the most efficient energy system and cheapest electricity. The electricity demand is expected to almost double, and the overall energy cost will increase by 20% compared to 2019. However, the technical challenges of seasonal electricity storage, without any reserves and redundancy, amounts to 20 TWh. Hydropower and PV without storage produce the cheapest electricity. Future nuclear fission technologies, e.g., molten salt Thorium breading reactor - currently still in an experimental stage–might become the most economical and least environmental impact solution for CO2 neutral continuous electricity production. The opportunities for a massive increase of hydroelectric production are limited, already shifting the use of water (9 TWh) from summer to winter is a great challenge. PV and hydrogen production in Switzerland have the advantage to provide approximately 75% of the electricity without seasonal storage leading to significantly lower electricity cost than from imported hydrogen or synthetic hydrocarbons. The most economical solution for aviation and reserves is imported bio-oil converted to synthetic Kerosene, for which large storages already exist.